Formulation, Characterization, and Pharmacokinetic Evaluation of Novel Glipizide-phospholipid Nano-complexes with Improved Solubility and Bio-availability - Rathor, Sandeep; Bhatt, Dinesh Chandra (Pharmaceutical Nanotechnology, 2022)
Background: The proposed study was aimed to formulate and evaluate the glipizidephospholipid nano-complex. Since glipizide is a poorly soluble drug, its complexation with phospholipids is an ideal approach to improving solubility. Methods: To improve the oral potency of glipizide, its phospholipid complex was prepared by employing the solvent evaporation method. The formulations were characterized using DSC, FTIR, PXRD, SEM, TEM, and hot stage microscopy (HSM). Solubility tests of the glipizidephospholipid nano-complex revealed a significant increase in aqueous solubility compared to glipizide's physical combination. The oral bioavailability of the glipizide-phospholipid nanocomplex was measured by using HPLC in Wistar rats’ plasma. FTIR and PXRD results revealed no significant interaction between the drug and the phospholipid in the formulation. SEM and TEM studies confirmed the morphology of the formulation assuring the conversion of crystalline form into an amorphous structure. Results: The glipizide-phospholipid nano-complex had a greater peak plasma concentration (5.2 vs. 3.8 g/mL), a larger AUC (26.31 vs. 19.55 μgh/L), and a longer T1/2 (2.1 vs. 4.1 h) than free glipizide, indicating that it improved drug dissolution rate. Conclusion: The outcomes suggested that a phospholipid complexation is a potential approach to increasing water-insoluble drugs' oral bioavailability.
Keywords: diabetes mellitus